2021
DOI: 10.3389/fpls.2021.781793
|View full text |Cite
|
Sign up to set email alerts
|

The History and Diversity of Rice Domestication as Resolved From 1464 Complete Plastid Genomes

Abstract: The plastid is an essential organelle in autotrophic plant cells, descending from free-living cyanobacteria and acquired by early eukaryotic cells through endosymbiosis roughly one billion years ago. It contained a streamlined genome (plastome) that is uniparentally inherited and non-recombinant, which makes it an ideal tool for resolving the origin and diversity of plant species and populations. In the present study, a large dataset was amassed by de novo assembling plastomes from 295 common wild rice (Oryza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 97 publications
1
25
0
Order By: Relevance
“…Before assembly of the short reads, plastome original reads were extracted by mapping all short reads to the nine plastomes as reference with BWA ( Li and Durbin, 2009 ) and SAMtools ( Danecek et al, 2021 ). Then the two plastomes were de novo assembled with SPAdes v3.15.2 ( Bankevich et al, 2012 ) as described in He et al (2021a) . Highly accurate annotation of organelle genomes was performed by using the Organellar Genome GeSeq tool ( Tillich et al, 2017 ) with subsequent manual correction.…”
Section: Methodsmentioning
confidence: 99%
“…Before assembly of the short reads, plastome original reads were extracted by mapping all short reads to the nine plastomes as reference with BWA ( Li and Durbin, 2009 ) and SAMtools ( Danecek et al, 2021 ). Then the two plastomes were de novo assembled with SPAdes v3.15.2 ( Bankevich et al, 2012 ) as described in He et al (2021a) . Highly accurate annotation of organelle genomes was performed by using the Organellar Genome GeSeq tool ( Tillich et al, 2017 ) with subsequent manual correction.…”
Section: Methodsmentioning
confidence: 99%
“…It is believed that Asian cultivated rice has the evolution progress of "One domestication and multiple origins" or "One origin and multiple interspecific introgressions." The indica, japonica, aus, and basmatic were parallel in origin, but gene introgressions among each other happened (He et al, 2021). The main domesticated genes were from japonica rice.…”
Section: Temperate and Tropical Japonica Were The Results Of Environm...mentioning
confidence: 98%
“…genomic studies suggested that the aus rice was originated from annual Oryza nivara (Kim et al, 2016), with distinct lineages of both nuclear and cytoplasm inheritance (Civán et al, 2015;Choi et al, 2017;He et al, 2021) and is relatively close to indica (Garris et al, 2005;Moner et al, 2018Moner et al, , 2020He et al, 2021).…”
Section: Temperate and Tropical Japonica Were The Results Of Environm...mentioning
confidence: 99%
See 2 more Smart Citations